Isoflavone in Postmenopausal Women - Are They Really Effective? A Prospective Case Control Study. - Bag, TS; Kyal, Amit; Saha, DP; Dutta, R; Mondal, S (Nepal Journal of Obstetrics and Gynaecology, 2013)
A prospective case control study was conducted at Medical College, Kolkata with the aim of evaluating the role of isoflavone( a class of phytoestrogen –plant compounds having the beneficial effects of estrogen but lesser risks and side effects) in postmenopausal women. 100 postmenopausal women (those who underwent total abdominal hysterectomy and bilateral salpingooopherectomy for different benign indications, aged between 40-50 years and who were menstruating before operation) were alternately distributed into two groups-Group A (n=50, received 60mg of isoflavone and 500mg of calcium per day for 6 months) and Group B (n=50, received 500mg of calcium per day only for 6 months). To evaluate the menopausal symptoms, the menopausal Kupperman index questionnaire was applied. Other outcomes measured were body mass index, blood pressure and lipid profile. Menopausal symptoms in Group A(those using isoflavones) were lower compared to Group B. The present study showed that Kupperman index decreased significantly in Group A (from 28.48 ± 2.03 to 16.32 ± 1.06 i.e. 45% decline) compared to Group B (from 24.56 ± 1.52 to 18.44 ± 1.11 i.e. 25% decline). No differences in blood pressure or body mass index were found during treatment between the two groups. . In our study total cholesterol, triglycerides and low-density lipoproteins (LDL) decreased significantly in Group A compared to Group B. Therefore our clinical study indicates that isoflavone can be an invaluable resource for postmenopausal women for combating menopausal symptoms. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 11-14 DOI: http://dx.doi.org/10.3126/njog.v7i1.8826